2014
DOI: 10.1186/2052-1847-6-28
|View full text |Cite
|
Sign up to set email alerts
|

Can supplementation with vitamin C and E alter physiological adaptations to strength training?

Abstract: BackgroundAntioxidant supplementation has recently been demonstrated to be a double-edged sword, because small to moderate doses of exogenous antioxidants are essential or beneficial, while high doses may have adverse effects. The adverse effects can be manifested in attenuated effects of exercise and training, as the antioxidants may shut down some redox-sensitive signaling in the exercised muscle fibers. However, conditions such as age may potentially modulate the need for antioxidant intake. Therefore, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 74 publications
2
20
0
1
Order By: Relevance
“…The detailed experimental design and limitations of the present study has already been described [26]. Results on muscle mass and more strength measurements have been published previously [25].…”
Section: Experimental Designmentioning
confidence: 93%
“…The detailed experimental design and limitations of the present study has already been described [26]. Results on muscle mass and more strength measurements have been published previously [25].…”
Section: Experimental Designmentioning
confidence: 93%
“…Six of the 38 participants entering the study dropped out (Paulsen et al . a ). Two participants experienced injuries unrelated to the study, and four withdrew because of a time schedule that was too busy.…”
Section: Methodsmentioning
confidence: 99%
“…This study was a double‐blinded, randomized controlled trial (Paulsen et al . a ). Tests and measurements were conducted before and after 10 weeks of heavy‐load traditional strength training at four exercise sessions per week (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Nakhostin-Roohi et al (13) have reported that single dose 1000 mg vitamin C prevented lipid peroxidation in sportsmen. Similarly, 1000 mg vitamin C supplementation has been useful affects in sportsmen (14). In clinical trials, it has been shown that vitamin C supplementation may be done by 1000 mg for 60 days at humans (15).…”
Section: Discussionmentioning
confidence: 99%